Causal inference of CLEC5A and ISG20 in atherosclerosis: integrating Mendelian randomization and eQTL evidence - Zhang, Ya; Tian, Qian; Zhu, Yuan; Wang, Tianhui; Yu, Yongchao; Wang, Lan; Shao, Lijuan; Mo, Xiangang (Frontiers in Immunology, 2025)
IntroductionAtherosclerosis (AS) is a vascular disorder characterized by lipid accumulation and chronic inflammation, with pathogenesis closely linked to genetic factors and immune regulatory mechanisms.MethodsThis study comprehensively identified ASassociated genes by integrating data from the Gene Expression Omnibus (GEO) database and expression quantitative trait locus (eQTL) analyses, complemented by Mendelian randomization (MR) analysis, followed by experimental validation of their functional roles.ResultsResults indicated significant upregulation of CLEC5A and ISG20 in patients with AS, with MR analysis revealing positive causal relationships between both genes and AS risk (CLEC5A: OR = 1.001, P = 0.047; ISG20: OR = 1.001, P = 0.030), while HOXA2 showed a negative causal association. Functional enrichment analysis highlighted CLEC5A and ISG20’s involvement in immune responses, inflammatory pathways, and lipid metabolism regulation. Experimental validation in oxidized low-density lipoprotein (ox-LDL)-stimulated macrophages and apolipoprotein E-deficient (ApoE–/–) mouse models consistently demonstrated significant upregulation of ISG20 expression (Western blot and RT-qPCR, P < 0.01). Immunofluorescence co-staining and immunohistochemistry confirmed its elevated expression in endothelial cell- and macrophage-rich regions of AS plaques.DiscussionThis study represents the first to elucidate the molecular mechanism by which ISG20 promotes AS progression through macrophage lipid accumulation and inflammatory responses, positioning it as a potential novel therapeutic target for AS.